2010
DOI: 10.4025/actascianimsci.v32i2.8800
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia e cinética de degradação do feno de Manihot glaziovii

Abstract: RESUMO.Avaliaram-se a composição química, o teor de compostos secundários, a degradabilidade in situ, a anatomia e a degradabilidade dos tecidos do feno de maniçoba, a partir de plantas em início de frutificação, oriundas de uma vegetação de caatinga em Ibimirim, Estado do Pernambuco. O caule apresentou células com variados graus de lignificação, destacando-se a presença de fibras gelatinosas, parênquima medular lignificado e espessas paredes celulares no xilema. As folhas se destacam pela presença da estrutur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
10
0
8
Order By: Relevance
“…Dentre as espécies forrageiras nativas da caatinga destacase a Maniçoba (Manihot pseudoglaziovii) uma Euphorbiaceae tóxica quando verde, no entanto, produtora de um feno que pode ser utilizado na alimentação dos pequenos ruminantes (ARAÚJO et al, 2004;SILVA et al, 2007;CASTRO et al, 2007;FRANÇA et al, 2010).…”
Section: Introductionunclassified
“…Dentre as espécies forrageiras nativas da caatinga destacase a Maniçoba (Manihot pseudoglaziovii) uma Euphorbiaceae tóxica quando verde, no entanto, produtora de um feno que pode ser utilizado na alimentação dos pequenos ruminantes (ARAÚJO et al, 2004;SILVA et al, 2007;CASTRO et al, 2007;FRANÇA et al, 2010).…”
Section: Introductionunclassified
“…It is mainly consumed by low-income people as a staple food source in Africa and the Americas, and includes 99 species (Nassar, 2002). Studies of the vegetative and reproductive anatomical characteristics of Manihot have been conducted in the last decade, and have focused on the stem (Graciano-Ribeiro et al, 2009;Nassar et al, 2008Nassar et al, , 2010a, root (Bomfim et al, 2011a,b), egg cell (Hashimoto-Freitas and Nassar, 2013), and leaves (França et al, 2010). However, knowledge of Manihot petiole anatomy is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The average lignin percentages of 11.0 and 17.10% respectively found by França et al (2010) and Barros et al (1990) can be explained by the phenological stage of the plant in the collection period, since in this study the EL presented an average of 11.8%, while LBS averaged 17.7%.…”
Section: Resultsmentioning
confidence: 62%
“…According to this author, the quality of this forage plant is higher after the beginning of the rainy period, which is also the ideal moment for haymaking because of the fewer indigestible components. França et al (2010) reported average NDF and ADF of 43.0 and 30.9% in a collection of leaves + branches for haymaking. Evaluating wild-cassava leaves and branches, Vasconcelos et al (2010) obtained mean percentages of 50.4 and 31.4% for NDF and ADF, respectively; these NDF values were much higher than those found in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation